The Position of the Turkish and Moroccan Second Generation in Amsterdam and Rotterdam The TIES Study in the Netherlands - Crul, Maurice; Heering, Liesbeth (IMISCOE Research, 2008)
The Dutch second generation of Turkish and Moroccan origin is coming of age and making a transition from education to the labour market. This first publication of the TIES Project (Towards the Integration of the European Second Generation) studies the social situation and views of this ethnic group, drawing on the research carried out in Amsterdam and Rotterdam in 2006-07 among the Dutch-born children of immigrants from Turkey and Morocco and a comparison group of young people (age 18-35) whose parents were born in the Netherlands. This title is available in the OAPEN Library - http://www.oapen.org.